Some Points of the Conception of Man and Humanity in Vydūnas’ Philosophy - Bagdonavičius, Vaclovas (Problemos, 1968)
Vydūnas (Vilius Storosta, 1868-1953), the outstanding representative of Lithuanian culture in East Prussia (former part of Germany), was a many-sided personality: a philosopher, a writer, a cultural worker, a publicist. Vydūnas’ creative work embraces the period from the last decade of the 19th century to the third decade of the 20th century. The struggle against German militarism was the mainspring of Vydūnas’ philosophical and dramatic works, which acquired great importance during the Great Patriotic War and the fight of Lithuanian people against German invaders. Being influenced by Indian philosophy Vydūnas points out the necessity of moral improvement of a personality and of all the people. Consciousness is the most important feature of man. It is brought to perfection in the course of creative activity. A man depends on his own behaviour and non on the mercy of fate. The triumph of humanity over inborn instincts in the inner world of man is the basis of morality.